Immobilization of enzymes and cells - Guisan, Jose M. (Humana Press, 2006)
The continuing rapid progress in work designed to improve the functional properties of enzymes and cells as industrial catalysts has led to this revised, updated, and expanded new edition of the warmly received initial edition of Immobilization of Enzymes and Cells. This long-awaited second edition contains new and simplified protocols useful for industrial applications, novel techniques that will prove useful now or in the near future, and protocols for the preparation of immobilized derivatives suitable for a wide variety of nonconventional reaction media. The authors also offer tools for the development of new immobilization techniques, methods for preparing immobilized derivatives for therapeutic and industrial use, and new chemical reactors designed to overcome the limitations of immobilized derivatives. The emphasis is on improving enzyme and cell properties via very simple immobilization protocols, along with the development of new and better methods. The protocols follow the successful Methods in Biotechnology series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Innovative and highly practical, Immobilization of Enzymes and Cells, Second Edition, affords biochemists, biotechnologists, and biochemical engineers a practical review of all the latest methods and tools-as well as optimized conventional techniques-needed to carry out successful research involving immobilizing enzymes and cells.